Problems affecting the accessibility of physicallychallenged individuals to intermediate public transport services in Oyo state, Nigeria - Ajayi, Julius (Logistics and sustainable transport, 2020)
The greatest challenge of physically-challenged individuals is mobility, thereby making access to public transportation essential to independent living for these individuals. The study was conducted in Oyo State. Multistage sampling method comprising purposive and simple random sampling was used to select a sample size of 226 students from three special education centres in the state. Findings revealed that factors such as operators’ impatience/discrimination, waiting time and lack of assistance were major problems that affects accessibility to IPTs. Furthermore, results showed that difficulties experienced by the physically-challenged individuals differ significantly by the nature of disability as evidenced by a chi-square value of 37.218, p<0.05. It was therefore recommended that government should listen more to these transport disadvantaged people living with disabilities and integrate their concerns/suggestions in the design, implementation and monitoring of transport infrastructure and services as well as providing sustainable transport means to their transport challenges.
Keywords: accessibility; dostopnost; intermediate public transport (IPTs); invalidi; javni prevoz; physically-challenged; transport disadvantaged; transportne pomanjkljivosti